Valuasi Ekonomi Wana Wisata Batu Kuda di Jawa Barat, Indonesia - Mantika M Warahmah; Endah Djuwendah (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Batu Kuda Forest Tourism Area is located in Bandung Regency, West Java. The area is a protected forest tourism destination that provides substantial environmental services and recreational benefits. However, the economic value of Batu Kuda Forest Tourism remains uncertain because most of the recreational benefits and environmental services provided by the area are not reflected in market mechanisms, causing its true economic value to be potentially underestimated. This study aimed to identify visitor characteristics and estimate the economic value of Batu Kuda Forest Tourism. This study applies the Individual Travel Cost Method approach by distributing questionnaires to 100 respondents using the accidental sampling technique. The results showed that the visitor profile was characterized by a relatively balanced gender composition, dominated by young adults aged 21–30 years, largely dominated by students with an average monthly income of less than IDR 1,000,000, and residing within 11–20 km of the tourist destination. The estimated consumer surplus was IDR 121,403 per visit, resulting in a total economic value of IDR 2.841.447.128 per year. These findings provide a new perspective as a basis for decision making in the management and development of tourism areas sustainably in the future.